Respon Khalayak dan Fungsi TVRI Sebagai TV Publik (Studi Kasus Program "Belajar Dari Rumah") - Arviani, Heidy; Santara, Marsha Vella; Dewi, Sandra Berliana (Global and Policy Journal of International Relations, 2020)
ABSTRACTAs public television, TVRI seeks to display a new identity by providing informative, educative, and positive entertainment programs for nation. The change of TVRIâ€™s status to Public Broadcasting Institution is expected to be able to accommodate the needs of the public as a container of public space (public sphere). This is proven during the Covid-19 pandemic, TVRI become an educational television program by broadcasting the â€œBelajar dari Rumahâ€ program in collaboration with Ministry of Education and Culture. This program displays subject matter for students from elementary to high school levels every Monday-Friday. â€œBelajar dari Rumahâ€ program is a form of TVRIâ€™s attention as education TV. The role of TVRI in this situation is very important, especially since internet penetration is still limited. Television has a wide reach throughout the country. This study aims to find out how the response of the audience, especially students who are the target audience of the program? Is this program effective in helping students, teachers, and parents? What are the obstacles encountered? The method used is descriptive qualitative with two data collection techniques namely online survey and in-depth interviews. The majority of respondents (61%) rated this program to be quite effective in helping them in the teaching-learning process. As many as 28.8% of respondents said it is effective. This program helps parents and teachers to follow the learning process of their children while at home. However, it is necessary to improve the interactive quality of show content, material for each level of education, and audio visual quality.Keywords: TVRI, Public TV, â€œBelajar dari Rumahâ€,Covid-19.Sebagai televisi publik, TVRI berupaya menampilkan identitas baru dengan memberi program yang informatif, edukatif, dan hiburan positif untuk bangsa. Perubahan status TVRI menjadi Lembaga Penyiaran Publik (LPP) diharapkan mampu mengakomodasi kebutuhan publik sebagai wadah ruang publik (publik sphere). Hal ini dibuktikan di saat masa tanggap darurat pandemi Covid-19, TVRI menjadi televisi pendidikan dengan menayangkan program â€œBelajar dari Rumahâ€ yang bekerja sama dengan Kementerian Pendidikan dan Kebudayaan. Program ini menayangkan materi pelajaran untuk jenjang Sekolah Dasar hingga Sekolah Menengah Atas setiap Senin-Jumat. Program â€œBelajar dari Rumahâ€ merupakan wujud perhatian TVRI sebagai TV Pendidikan. Peran TVRI dalam situasi ini sangat penting, terlebih karena penetrasi internet masih terbatas. Televisi mempunyai jangkauan yang luas ke seluruh negeri. Penelitian ini bertujuan untuk mengetahui bagaimana respon khalayak terutama para siswa yang menjadi target khalayak dari program â€œBelajar dari Rumahâ€? Apa program ini efektif membantu para siswa, guru, dan orang tua? Apa saja kendala yang dihadapi? Metode yang digunakan adalah kualitatif deskriptif dengan dua teknik pengumpulan data, yakni survei online & wawancara mendalam. Mayoritas responden (61%) menilai program â€œBelajar dari Rumahâ€ cukup efektif membantu mereka dalam proses belajar-mengajar. Sebanyak 28,8% responden menyatakan efektif. Dan sisanya sebanyak 5,1% responden mengaku tidak efektif. Program ini membantu orang tua dan guru untuk mengikuti proses belajar anaknya selama di rumah. Namun, perlu ditingkatkan kualitas interaktif konten acara, materi untuk tiap jenjang pendidikan, dan kualitas audio visual.Kata-Kata Kunci : TVRI, TV Publik, â€œBelajar dari Rumahâ€, Covid-19.